Antimicrobial Study against Seven Cycles Compounds Derivatives from Pyrimidine - Aseel Fadhil Kareem1 , Hasan Thamer Ghanim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The current study involves preparing newly pyrimidine derivative compound with seven membrane rings and used it to explain the antimicrobial activity of it against four isolates of four types of G+ & G– pathogenic bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Klebsiella pneumonia) respectively, with two types of fungi (Aspergilus niger & Penicillium chrysogenum) by using four different concentrations (5, 10 , 15 & 20 mg/ml-1). The characterizations and properties of this compound have biological and pharmacological functions through the inhibition the growth of many types of organisms.